Identifying Genetic Risk Factors for Diabetic Macular Edema and the Response to Treatment. (16th November 2020) - Gurung, Rajya L.; FitzGerald, Liesel M.; McComish, Bennet J.; Verma, Nitin; Burdon, Kathryn P.
Abstract : Diabetic retinopathy (DR) is the most common microvascular complication of diabetes mellitus (DM). DR is complex and the term encompasses several clinical subtypes of diabetic eye disease, including diabetic macular edema (DME), the most frequent cause of central vision loss in DR patients. Both genetic and environmental factors contribute to the pathophysiology of DR and its subtypes. While numerous studies have identified several susceptibility genes for DR, few have investigated the impact of genetics on DME susceptibility. This review will focus on the current literature surrounding genetic risk factors associated with DME. We will also highlight the small number of studies investigating the genetics of response to antivascular endothelial growth factor (anti-VEGF) injection, which is used to treat DME.